Photocatalytic Reduction of CO2 Into Methanol Over CuFe2O4/TiO2 under Visible Light Irradiation - Uddin, M. Rahim; Khan, Maksudur R.; Rahman, M. Wasikur; Yousuf, Abu; Cheng, C. K. (Springer, 2015)
The present study aims to focus the photocatalytic reduction of carbon dioxide (CO2) into methanol on TiO2 loaded copper ferrite (CuFe2O4) photocatalyst under visible light (500 W xenon lamp) irradiation. In this perspective, CuFe2O4 and CuFe2O4/TiO2 photocatalysts were synthesized following the sol–gel method from copper(II) nitrate, Cu(NO3)2·3H2O (99 %) and iron(III) nitrate, Fe(NO3)3·9H2O (99 %) as precursors. The phases and crystallite size of the photocatalysts were characterized by X-ray diffraction (XRD), morphology by scanning electron microscopy (SEM), absorption spectrum by ultraviolet–visible spectroscopy (UV–Vis), electron–hole (e−/h+) recombination process by photoluminescence spectrophotometer, and elemental compositions by energy dispersive X-ray spectroscopy (EDX) instruments. The loading of TiO2 on CuFe2O4 enhanced the photocatalytic activity in the visible light range. The enhanced photoactivity in CuFe2O4/TiO2 semiconductor catalyst can be attributed to interfacial transfer of photogenerated charges, which led to effective charge separation and inhibited the recombination of photogenerated electron–hole (e−/h+) pairs. Methanol was observed as the main product over CuFe2O4/TiO2 and the photocatalytic activity of CuFe2O4/TiO2 for CO2 reduction was found to be about three times higher (651 μmol/gcat L) than that of CuFe2O4 photocatalyst which might be due to the modification of band gap through TiO2 loading.